2021
DOI: 10.3389/fmicb.2021.634325
|View full text |Cite
|
Sign up to set email alerts
|

How Tillage and Crop Rotation Change the Distribution Pattern of Fungi

Abstract: Massive sequencing of fungal communities showed that climatic factors, followed by edaphic and spatial variables, are feasible predictors of fungal richness and community composition. This study, based on a long-term field experiment with tillage and no-tillage management since 1995 and with a crop rotation introduced in 2009, confirmed that tillage practices shape soil properties and impact soil fungal communities. Results highlighted higher biodiversity of saprotrophic fungi in soil sites with low disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…However, in the absence of direct experimental evidence, we cannot explain the positive associations between SOM and the saprotrophic decomposers phyla Kickxellomycota, Chitridiomycota, and Morteriellomycota. Despite our observations being in line with previous studies in agricultural soils (64,65), the causal mechanism behind the correlations remains uncertain, and further evidence is necessary to disentangle the role of minor phyla in soil C cycling, EPS synthesis and aggregate formation.…”
Section: Discussionsupporting
confidence: 69%
“…However, in the absence of direct experimental evidence, we cannot explain the positive associations between SOM and the saprotrophic decomposers phyla Kickxellomycota, Chitridiomycota, and Morteriellomycota. Despite our observations being in line with previous studies in agricultural soils (64,65), the causal mechanism behind the correlations remains uncertain, and further evidence is necessary to disentangle the role of minor phyla in soil C cycling, EPS synthesis and aggregate formation.…”
Section: Discussionsupporting
confidence: 69%
“…Understanding the composition, traits, and functions of soil organisms, as well as their ecological interactions, is imperative to understand which agricultural practices can maintain plant biodiversity, soil health, and productivity (van der Heijden et al, 1998 ; Francaviglia et al, 2004 ; Zhang J. et al, 2020 ). Recently, it was found that crop diversification and soil disturbance strongly impact on microbiome functional diversity, as plant residues play a substantial role in defining the assortment of microbial species (Figueiredo Santos and Olivares, 2021 ; Orrú et al, 2021 ). The fungi:bacteria ratio in soil microbial community depends on environmental changes and its impact on soil functioning is a key element in the assessment of microbiome functional diversity (Strickland and Rousk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method allows us to focus on multiple species (i.e., bacterial and fungi communities) and their related functionality in soil (Moscatelli et al, 2018 ), for example, nutrient availability, stress resistance, or plant diseases (Sirangelo and Calabrò, 2020 ). The use of NGS to investigate agricultural soils, where crop diversification and no tillage, was applied for 10 years showed that some fungal species worked as indicators of soil disturbance in intensively tilled soils, while others seemed to be mostly associated with chemical characteristics of plant residues accumulated on soil surface (Ashworth et al, 2017 ; Orrú et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of wheat and maize rotation, it was found that the effect of tillage on the depth decay of bacterial community was significantly smaller than that under no tillage, and the depth decay of fungal community was significantly greater under reduced tillage than that under tillage and no tillage ( Sun et al, 2018 ). Furthermore, the plowed soil could produce an even distribution of fungal species ( Orrù et al, 2021 ). And the vertical rotation cultivation was helpful to improve the yield and profit of drought resistance of potato ( Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%